2001
DOI: 10.1309/p2m2-jea3-yyqf-0p38
|View full text |Cite
|
Sign up to set email alerts
|

Hyperplasia of Mantle/Marginal Zone B Cells With Clear Cytoplasm in Peripheral Lymph Nodes

Abstract: We describe 35 peripheral lymph nodes classified as mantle cell/marginal zone B-cell hyperplasia with clear cells using morphologic and immunologic findings. For the purpose of this study, we obtained clinical follow-up information and performed immunoglobulin gene rearrangement studies on paraffin sections by polymerase chain reaction. Architecturally, the nodes were suggestive of a benign process: no pericapsular infiltration, sinuses readily identified, scattered reactive follicles present, and paracortical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 17 publications
3
10
0
Order By: Relevance
“…Recently, Hant et al reported hyperplasia of mantle zone lymphocytes with clear cytoplasm in peripheral lymph nodes and discussed the problems of differentiating nodal marginal zone B-cell lymphoma or mantle cell lymphoma (MCL) [5]. The present three cases confirmed this observation in reactive lymphoid hyperplasia of the terminal ileum.…”
Section: Discussionsupporting
confidence: 82%
“…Recently, Hant et al reported hyperplasia of mantle zone lymphocytes with clear cytoplasm in peripheral lymph nodes and discussed the problems of differentiating nodal marginal zone B-cell lymphoma or mantle cell lymphoma (MCL) [5]. The present three cases confirmed this observation in reactive lymphoid hyperplasia of the terminal ileum.…”
Section: Discussionsupporting
confidence: 82%
“…2 MCL with a mantle zone growth pattern can be confused with either marginal zone lymphoma or reactive follicular hyperplasia. 6 Our study presents two cases of MCL with a pure mantle zone pattern, representing an in situ-like MCL.…”
mentioning
confidence: 95%
“…Finally, as suggested by Hunt et al, 28 reactive lymph node lesions may rarely show mantle cell hyperplasia with clear cytoplasm. In our study, an association of mantle cell hyperplasia with clear cytoplasm and LV of HVCD has a relatively high incidence (27%).…”
Section: -21mentioning
confidence: 68%